2006
DOI: 10.1248/bpb.29.410
|View full text |Cite
|
Sign up to set email alerts
|

GATA-4 Gene Organization and Analysis of Its Promoter

Abstract: The GATA DNA-binding protein family in mammals has two tandem zinc fingers separated by 29 amino acid residues [(CX 2 C)X 17 (CX 2 C)]-X 29 -[(CX 2 C)X 17 (CX 2 C)] in the middle of the molecule. These fingers are essential for both DNA binding and interaction with other regulatory factors.1,2) The mammalian GATA family has six members. They are divided in two subgroups; one group consists of GATA-1, -2 and -3, which play crucial roles in the development and gene regulation of hematopoietic lineage cells. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 77 publications
6
27
0
1
Order By: Relevance
“…Guittot et al (28) show that the first 5-kb of Gata4 promoter-enhancer sequence was sufficient to direct gene expression in the adult mouse heart, although they did not examine the activity of this fragment during embryonic and postnatal development. Recently, two GC boxes and an E box between Ϫ124 bp and Ϫ36 bp of the mouse Gata4 promoter have been shown to be important for its expression during differentiation of P19.CL6 cells into beating cardiomyocyte-like cells in vitro (29). Results of our present studies showed that Klf4 selectively bound to the Gata4 promoter region in the heart of control mice but not conditional Klf4 knock-out mice, as determined by in vivo ChIP assays.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Guittot et al (28) show that the first 5-kb of Gata4 promoter-enhancer sequence was sufficient to direct gene expression in the adult mouse heart, although they did not examine the activity of this fragment during embryonic and postnatal development. Recently, two GC boxes and an E box between Ϫ124 bp and Ϫ36 bp of the mouse Gata4 promoter have been shown to be important for its expression during differentiation of P19.CL6 cells into beating cardiomyocyte-like cells in vitro (29). Results of our present studies showed that Klf4 selectively bound to the Gata4 promoter region in the heart of control mice but not conditional Klf4 knock-out mice, as determined by in vivo ChIP assays.…”
Section: Discussionsupporting
confidence: 53%
“…Although little is known regarding the transcriptional control of the Gata4 gene, results of several studies showed that multiple GC boxes and an E box within its promoter (Fig. 7A) were important for expression (27)(28)(29). We found a consensus Klf4 binding site at Ϫ125/Ϫ119 bp, in close proximity to four GC boxes and an E box (Fig.…”
Section: In Vivo Chip Assays Demonstrated Klf4 Binding To the Gata4 Pmentioning
confidence: 59%
“…Regarding gonadal expression, we also previously reported that the same 5-kb fragment controls reporter gene expression specifically in the testes and more precisely in Sertoli cells from embryonic to adult stages [20,21]. A detailed analysis of this 5-kb fragment revealed an evolutionary conserved Ebox element (CACGTG) located near the transcriptional start site and we found this regulatory element to be critical for Gata4 promoter activity in vitro, being bound by USF2 in gonadal cell lines [20,22]. However, the importance of this Ebox motif in vivo is unknown.…”
Section: Introductionsupporting
confidence: 66%
“…The PCR products were size-separated on an agarose gel (1%) and DNA bands were visualized with ethidium bromide. 13) Total RNA of HeLa and HEK-293 cells 14) was also used. Expression Plasmids for Mouse Mat-8 The expression plasmid for mouse Mat-8, pMat-8-DsRed, 11) was digested with NotI and PspOMI to remove the DsRed moiety.…”
Section: )mentioning
confidence: 99%